2022
DOI: 10.3390/ijms231710172
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and Glucose Metabolism in Cancer

Abstract: Connexins are a family of transmembrane proteins that regulate diverse cellular functions. Originally characterized for their ability to mediate direct intercellular communication through the formation of highly regulated membrane channels, their functions have been extended to the exchange of molecules with the extracellular environment, and the ability to modulate numerous channel-independent effects on processes such as motility and survival. Notably, connexins have been implicated in cancer biology for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 326 publications
(343 reference statements)
0
7
0
Order By: Relevance
“…Recently, Cx43 has been characterized as a valuable diagnostic and prognostic biomarker in various cancers [14]. In our study, we employed ROC curve analysis and Kaplan-Meier survival curve analysis to assess the diagnostic and prognostic significance of GJA1 in pan-cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cx43 has been characterized as a valuable diagnostic and prognostic biomarker in various cancers [14]. In our study, we employed ROC curve analysis and Kaplan-Meier survival curve analysis to assess the diagnostic and prognostic significance of GJA1 in pan-cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented forms of Cx43 have been implicated in exerting a vital role in the regulation of gene transcription and cell growth [11][12][13]. In addition, Cx43 expression has been observed to be associated with both cancer promotion and suppression, exerting significant influences on carcinogenesis, cancer progression, and metastasis [14]. For example, previous studies have shown that Cx43 expression was significantly decreased in gastric cancer, melanoma cancer [15], pancreatic cancer [16,17], lung cancer [18,19], chronic B-cell leukemia [20], prostate cancer [21], breast cancer [22][23][24][25], and thyroid cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with the oxidative phosphorylation pathway, the conversion of glucose to lactic acid produces less energy. It is insufficient to maintain the energy supply for cancer cells, and then more glucose will be consumed ( Chakraborty et al, 2021 ; Jones and Bodenstine, 2022 ). The kidneys contain a large number of glucose transporters, which participate in glucose reabsorption, excretion and other metabolic pathways.…”
Section: The Role Of Metabolism In Rccmentioning
confidence: 99%
“…Once VHL is lost, the degradation process of transcription factors will be weakened. And then HIF-1α transcription factors under normoxic conditions will be accumulated, and makes cells in a pseudohypoxic state, leading to the changes in the metabolic process ( Appelhoff et al, 2004 ; Chatzopoulos et al, 2022 ; Chen et al, 2022a ; Jones and Bodenstine, 2022 ). The mutation mediated by VHL/HIF-1α can up-regulate the expression of glucose transporter 1 (GLUT-1) in ccRCC, and the glycolysis related gene lactate dehydrogenase A (LDHA) also strongly expresses in several tumor cell lines and RCC.…”
Section: The Role Of Metabolism In Rccmentioning
confidence: 99%
“…Glucose is a vital carbon substrate for generating energy and metabolic intermediates ( 146 ). Cancer cells frequently rely on glycolytic metabolism for maintenance; nonetheless, cellular reprogramming of metabolic processes frequently occurs in developing tumors when blood perfusion is constrained ( 147 ). For instance, circGOT1 functions as an oncogene in ESCC, which promotes aerobic glycolysis through the miR-606/GOT1 axis, acting as an mRNA sponge ( 86 ).…”
Section: Circrnas As a Novel Regulator Of Tumor Microenvironment In Esccmentioning
confidence: 99%